Identity Negotiation And Resistance In The Short Story 'Rose In The Tiger Canal': A Review Of Feminism Poscocolonial - Eva Rosita; Prima Gusti Yanti (Eduvest - Journal of Universal Studies, 2024)
This study examines the negotiation of identity and female resistance in the short story Mawar di Kanal Macan by Iksaka Banu, focusing on the dual oppression faced by women in colonial and postcolonial contexts. Using a descriptive-analytical method and a postcolonial feminist approach, the research explores how colonial and patriarchal power structures shape women's identities and incite resistance. Drawing on theories of identity, subalternity, and hybridity, the analysis investigates how women in subaltern positions negotiate their identities within dominant power structures. Furthermore, it examines how hybridity and intersectionality create spaces for resistance through both subtle and overt actions. The findings reveal that the main character, Adelheid Ewald, navigates complex identity negotiations due to the intersecting influences of colonial and patriarchal dominance, with resistance manifesting in legal and symbolic forms. These insights contribute to postcolonial feminist discourse in Indonesia, offering a deeper understanding of how women assert their agency despite operating within layered systems of oppression. The study suggests further exploration of other literary works that engage similar themes to expand discussions on identity and resistance in postcolonial societies.